Science for citizenship: advances to face the challenges of training scientifically literate citizens in Chile - Ramos Araya, Maria Cecilia (2023)
In 2020, the subject Science for Citizenship was included in the Chilean school curriculum in response to the global challenges to move towards scientific literacy to encourage citizens to participate in decision making for their personal lives or in their participation socially. The objective of the research was to understand the contributions of the subject Science for Citizenship to the Chilean school curriculum to advance toward scientific literacy.This article presents a descriptive analysis of the Chilean educational policy documents, based on the review of the purposes, approaches, modules, and learning objectives of the Science for Citizenship subject. The findings show that the curriculum promotes the acquisition, use, critical analysis, creation, and communication of information that addresses science and technology.